Budget efficient 3D-mesh of engravings using photometric stereo - Heinmetz, Edvard (My University, 2025)
This paper describes a process for calculating approximate light positions in a photo set captured of an inscribed wall, with the purpose of applying photometric stereo. The light sources across the photo set are of constant intensity and their positions are inferred using one reflective indicator sphere and the lighting of the wall. The light positions are then used to create a depth map of the wall in an optimization scheme that alternates between depth and albedo values. Various strategies for using the depth map to highlight and isolate inscriptions are then applied.
Keywords: photometric stereo; mesh; engravings; optimization